O SAGRADO E AS CIRCUNSTÂNCIAS: RESTAURAÇÃO DA CAPELA NOSSA SENHORA DA CONCEIÇÃO DO ANTIGO ENGENHO PENHA. - Pina Neto, Reginaldo Passos (2018)
The Nossa Senhora da Conceição Chapel of the ancient mill Penha, located in the rural area of Riachuelo city of Sergipe, is one of the most important buildings in the religious architecture of Sergipe. Built between the end of the 18th century and the beginning of the 19th century, the monument is today the only remnant of the rural complex which gave it origin. Heritage listed in the Institute of the National Historical and Artistic Patrimony - Iphan, since 1943, the chapel stands in an advanced state of degradation, with the loss of all its integrated assets and with much of its collapsed east side facade, thus creating a huge gap in the building and landscape. At first, this work seeks to investigate the process of architectural and spatial composition of the mill, the history of the building since its construction, the diagnosis of existing pathologies, in order to understand the causes that led to its current state and the changes that occured in its surroundings. Based on this study, a proposal will be developed for restorative intervention of the chapel and the reinsertion of the building in the rural landscape in which it is implanted. In this way, we understand the need to recompose the missing gaps to seek the rescue of the typological plot and the spatiality of the monument, evidencing the protection of the property in its integrity and its adaptation to the local community activities.